Compared to Palliative Care, Working in Intensive Care More than Doubles the Chances of Burnout: Results from a Nationwide Comparative Study - Martins Pereira, Sandra (PLoS One, 2016)
INTRODUCTION: Professionals working in intensive and palliative care units, hence caring for patients at the end-of-life, are at risk of developing burnout. Workplace conditions are determinant factors to develop this syndrome among professionals providing end-of-life care. OBJECTIVES: To identify and compare burnout levels between professionals working in intensive and palliative care units; and to assess which workplace experiences are associated with burnout. METHODS: A nationwide, multicentre quantitative comparative survey study was conducted in Portugal using the following instruments: Maslach Burnout Inventory–Human Services Survey, Questionnaire of workplace experiences and ethical decisions, and Questionnaire of socio-demographic and professional characteristics. A total of 355 professionals from 10 intensive care and 9 palliative care units participated in the survey. A series of univariate and multivariate logistic regression analyses were performed; odds ratio sidelong with 95% confidence intervals were calculated. RESULTS: 27% of the professionals exhibited burnout. This was more frequent in intensive care units (OR = 2.525, 95% CI: 1.025–6.221, p = .006). Univariate regression analyses showed that higher burnout levels were significantly associated with conflicts, decisions to withhold/withdraw treatment, and implementing palliative sedation. When controlling for socio-demographic and educational characteristics, and setting (intensive care units versus palliative care units), higher burnout levels were significantly and positively associated with experiencing conflicts in the workplace. Having post-graduate education in intensive/palliative care was significantly but inversely associated to higher burnout levels. CONCLUSIONS: Compared to palliative care, working in intensive care units more than doubled the likelihood of exhibiting burnout. Experiencing conflicts (e.g., with patients and/or families, intra and/or inter-teams) was the most significant determinant of burnout and having post-graduate education in intensive/palliative care protected professionals from developing this syndrome. This highlights the need for promoting empowering workplace conditions, such as team empowerment and conflict management. Moreover, findings suggest the need for implementing quality improvement strategies and organizational redesign strategies aimed at integrating the philosophy, principles and practices of palliative care in intensive care units.